Jack Ward Thomas : The Journals of a Forest Service Chief - Thomas, Jack Ward (Book collections on Project MUSE., 2004)
He considers the timber salvage rider and its linkage to forest health, the Department of Justice and Counsel on Environmental Quality influence on Forest Service policies, and interagency management for the Columbia River Basin." "Woven throughout these excerpts from his diary is Thomas's conviction that the effective, ethical management of wildlife depends on how the management effort is situated within the broader human context, with all its intransigence and unpredictability."--Jacket.